NMR resonance assignments of a hypoallergenic isoform of the major birch pollen allergen Bet v 1 - Ahammer, Linda (Biomol NMR Assign, 2017)
In Northern America and Europe a great number of people are suffering from birch pollen allergy and pollen related food allergies. The trigger for these immunological reactions is the 17.5 kDa major birch pollen allergen Bet v 1, which belongs to the family of PR-10 (pathogenesis-related) proteins. In nature, Bet v 1 occurs as a mixture of various isoforms that possess different immunological properties despite their high sequence identities. Bet v 1.0102 (Bet v 1d), which is investigated here, is a hypoallergenic isoform of Bet v 1 and a potential candidate for allergen-specific immunotherapy. We assigned the backbone and side chain (1)H, (13)C and (15)N resonances of this protein and predicted its secondary structure. The NMR-chemical shift data indicate that Bet v 1.0102 is composed of three α-helices and a seven stranded β-sheet, in agreement with the known structure of the hyperallergenic isoform Bet v 1.0101 (Bet v 1a). Our resonance assignments create the foundation for detailed characterization of the dynamic properties of Bet v 1 isoforms by NMR relaxation measurements.